LM02 trial Perioperative treatment with panitumumab and FOLFIRI in patients with wild-type RAS, potentially resectable colorectal cancer liver metastases—a phase II study - Piringer, Gudrun; Gruenberger, Thomas; Thaler, Josef; Kührer, Irene; Kaczirek, Klaus; Längle, Friedrich; Viragos-Toth, Istvan; Amann, Arno; Eisterer, Wolfgang; Függer, Reinhold; Andel, Johannes; Pichler, Angelika; et al. (Frontiers in Oncology, 2023)
Background Twenty percent of colorectal cancer liver metastases (CLMs) are initially resectable with a 5-year survival rate of 25%–40%. Perioperative folinic acid, 5-fluorouracil, oxaliplatin (FOLFOX) increases progression-free survival (PFS). In advanced disease, the addition of targeting therapies results in an overall survival (OS) advantage. The aim of this study was to evaluate panitumumab and FOLFIRI as perioperative therapy in resectable CLM. Methods Patients with previously untreated, wild-type Rat sarcoma virus (RAS), and resectable CLM were included. Preoperative four and postoperative eight cycles of panitumumab and folinic acid, 5-fluorouracil, irinotecan (FOLFIRI) were administered. Primary objectives were efficacy and safety. Secondary endpoints included PFS and OS. Results We enrolled 36 patients in seven centers in Austria (intention-to-treat analyses, 35 patients). There were 28 men and seven women, and the median age was 66 years. About 91.4% completed preoperative therapy and 82.9% underwent liver resection. The R0 resection rate was 82.7%. Twenty patients started and 12 patients completed postoperative chemotherapy. The objective radiological response rate after preoperative therapy was 65.7%. About 20% and 5.7% of patients had stable disease and progressive disease, respectively. The most common grade 3 adverse events were diarrhea, rash, and leukopenia during preoperative therapy. One patient died because of sepsis, and one had a pulmonary embolism grade 4. After surgery, two patients died because of hepatic failure. Most common grade 3 adverse events during postoperative therapy were skin toxicities/rash and leukopenia/neutropenia, and the two grade 4 adverse events were stroke and intestinal obstruction. Median PFS was 13.2 months. The OS rate at 12 and 24 months were 85.6% and 73.3%, respectively. Conclusions Panitumumab and FOLFIRI as perioperative therapy for resectable CLM result in a radiological objective response rate in 65.7% of patients with a manageable grade 3 diarrhea rate of 14.3%. Median PFS was 13.2 months, and the 24-month OS rate was 73.3%. These data are insufficient to widen the indication of panitumumab from the unresectable setting to the setting of resectable CLM.